Project report - months 1 - 18, Deliverable 1.2 of the H2020 project SafetyCube. - Pete Thomas; Ashleigh Filtness; Rachel Talbot; Alice Magrin (2016)
This report, D1.2 Project Report - months 1 – 18, provides an overview of the work undertaken in the SafetyCube project. At the time of the preparation of the project the reporting requirements were not known and an internal mid-term evaluation of the project was considered to be helpful to the project team. Since then the formal project reporting requirements have become known and the internal mid-term evaluation of the project has been superseded by the Mid-term Project Review which covers M1 – M18. The objectives for the first 18 months of the project were to: 1. Implement the project management framework to support communication between partners and achievement of project objectives. 2. Establish a project dissemination and consultation platform to ensure all stakeholders can remain informed of the project progress and can contribute to the DSS. 3. Develop the methodological framework of the DSS, and process for extracting data on risks and measures. 4. Estimate the numbers of seriously injured traffic casualties in Europe and the resulting health impacts. 5. Define the functionality of the DSS and prepare the underlying structure. Very good progress has been made in the first 18 months of the project and all objectives have been achieved. Notably; 1. The project now has a very effective management framework that is focussed on: • The project coordinator and a dedicated project administrator. • Monthly Work Package (WP) Leaders meetings for routine decision making. • Regular WP partner meetings. • Periodic full partner plenary meetings. • A dedicated web conferencing system to facilitate communication together with a central web-based document repository. 2. A dissemination platform has been established to facilitate communication between the project and future DSS users. • The project website (www.safetycube-project.eu) provides information about the project and news of recent developments. • A newsletter, published typically four times each year, provides more detailed information to recipients. • A series of stakeholder consultation workshops have provided the project team with very useful guidance regarding the functionality and content of the DSS. 3. The methodological framework for the DSS has been established and data on risks has been evaluated and recorded for entry to the DSS. • The procedure to be used to record details of risks and measures from studies has been defined. • A sophisticated data entry template has been developed to provide a consistent means to gather data for entry onto the database and to enable an automatic quality check of template use. • A total of 600 studies have been reviewed and data of 3,500 risks has been entered onto the templates. The studies cover road user, infrastructure and vehicle risks. • A total of 60 topic syntheses have been prepared to provide summaries and critical evaluation of the existing knowledge about road safety risks. The studies cover road user, infrastructure and vehicle risks. 4. Important advances have been made regarding the enumeration of serious injuries and the societal level impact. • With the assistance of EC DG-MOVE a strong collaboration has been established with the EU CARE experts group representing the Member States. • The methods used across the EU to estimate the numbers of seriously injured casualties have been reviewed and the comparability assessed. • Recommendations for approaches to improve accuracy of serious injury counting have been made. 5. The structure and functionality of the DSS has been developed and a provisional “look and feel” prepared. • A comprehensive taxonomy of risks and measures has been prepared to provide the internal structure of the DSS. • The basic functionality of the DSS has been specified and entry points, search methodologies and output descriptions have been prepared. • Wireframe screens have been prepared to illustrate the possible appearance of the DSS.